ChemInform Abstract: Developing Catalytic Applications of Cooperative Bimetallics: Competitive Hydroamination/Trimerization Reactions of Isocyanates Catalyzed by Sodium Magnesiates. Issue 3 (21st January 2014) - Hernan‐Gomez, Alberto; Bradley, Tyne D.; Kennedy, Alan R.; Livingstone, Zoe; Robertson, Stuart D.; Hevia, Eva
Abstract The catalytic behavior of the applied catalyst can be tuned by controlling the steric bulk of the isocyanates employed.